2009
DOI: 10.1158/0008-5472.can-08-4657
|View full text |Cite
|
Sign up to set email alerts
|

GnRH-II Antagonists Induce Apoptosis in Human Endometrial, Ovarian, and Breast Cancer Cells via Activation of Stress-Induced MAPKs p38 and JNK and Proapoptotic Protein Bax

Abstract: Recently, we could show that gonadotropin-releasing hormone (GnRH)-II antagonists induce apoptosis in human endometrial, ovarian, and breast cancer cells in vitro and in vivo. In the present study, we have ascertained receptor binding and effects of GnRH-II antagonists on mitogenic signal transduction and on activation of proapoptotic protein Bax. The GnRH-II antagonists tested showed EC 50 values for GnRH-I receptor binding in the range of 1 to 2 nmol/L. The GnRH-II agonist [D-Lys 6 ]GnRH-II showed an EC 50 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 42 publications
4
51
0
2
Order By: Relevance
“…In numerous cell types, JNK and p38 MAPK contribute to the induction of apoptosis, whereas ERK inhibits apoptotic processes (30)(31)(32). In the present study, treatment with quercetin enhanced the protein levels of phosphorylated ERK1/2, whereas it reduced the protein levels of phosphorylated JNK.…”
Section: Discussionsupporting
confidence: 51%
“…In numerous cell types, JNK and p38 MAPK contribute to the induction of apoptosis, whereas ERK inhibits apoptotic processes (30)(31)(32). In the present study, treatment with quercetin enhanced the protein levels of phosphorylated ERK1/2, whereas it reduced the protein levels of phosphorylated JNK.…”
Section: Discussionsupporting
confidence: 51%
“…Previous work showed that nanomolar concentrations of GnRH-II antagonists induce apoptotic cell death in human endometrial, ovarian, and breast cancer cells in vitro and in vivo via stress-induced MAPKs p38-and JNK-induced activation of the proapoptotic protein Bax, loss of mitochondrial membrane potential, release of cytochrome c, and activation of caspase-3 [16][17][18]. Furthermore, we demonstrated that GnRH-II antagonists bind to the GnRH-I receptor and are clear antagonists at the GnRH-I receptor [17]. Recently, we showed that invasion of breast cancer cells through an artificial basement membrane was increased when they were cocultured with human primary osteoblasts (hOB) [19].…”
Section: Introductionmentioning
confidence: 99%
“…17,28,29 Now we could show that the combination of both glycolysis inhibition and GnRH receptor-targeted chemotherapy using AESZ-108 results in a significantly increased antiproliferative effect compared with the single agents. Combination of glycolysis inhibitor 2DG and GnRH receptor-targeted hormone therapy using GnRH-II antagonist [Ac-D2Nal 1 , D-4Cpa 2 , D-3Pal 3,6 , Leu 8 , D-Ala 10 ]GnRH-II which induces apoptosis in vitro and in vivo 18,19 gave comparable results. However, due to the smaller antitumor effect of a GnRH-II antagonist compared with cytotoxic AESZ-108, the additive effect was more moderate as expected.…”
Section: Discussionmentioning
confidence: 99%
“…The GnRH-II antagonist [Ac-D2Nal 1 , D-4Cpa 2 , D-3Pal 3,6 , Leu 8 , D-Ala 10 ]GnRH-II was developed by us and synthesized by Peptide Specialty Laboratories GmbH (Heidelberg, Germany). 19 The cytotoxic GnRH agonist AEZS-108 (AN-152), which consists of 1 molecule of doxorubicin-14-0-hemiglutarate linked covalently to the D-amino group of the D-Lys 6 moiety of [D-Lys 6 ]GnRH, 26 was a gift from Aeterna Zentaris GmbH (Frankfurt, Germany).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation